México y Chile: Paradojas democráticas e injusticias distributivas - Díaz, Carlos Alberto (Revista de Sociología, 2016)
State distributive configurations, dictatorial institutional legacies and/or authoritarian, corruption and violence, influence on the cultural dimensions of democracy and inequality in Mexico and Chile. These factors have historically acted as dilators inequality through dark political networks, which are present in different ways in the development of their countries and their economies. When illegal and informal features of these stents are valued positively, solidarity, participation in public affairs and the possibility that the contradictions of inequality become visible in public space are altered.